Participatory action research to develop and implement multicomponent, multilevel strategies for implementing colorectal cancer screening interventions in American Indian communities in New Mexico - Prajakta Adsul; Kevin English; Cheyenne Jim; V. Shane Pankratz; Nicholas Edwardson; Judith Sheche; Joseph Rodman; Jimmie Charlie; John Pagett; Jonathan Trujillo; Jillian Grisel-Cambridge; Steven Mora; et al. (Implementation Science Communications, 2024)
Abstract Background Despite the effectiveness of colorectal cancer (CRC) screening, American Indians (AIs) have low screening rates in the US. Many AIs receive care at Indian Health Services, Tribal, and Urban Indian (I/T/U) healthcare facilities, where published evidence regarding the implementation of CRC screening interventions is lacking. To address this gap, the University of New Mexico Comprehensive Cancer Center and the Albuquerque Area Southwest Tribal Epidemiology Center collaborated with two tribally-operated healthcare facilities in New Mexico with the goal of improving CRC screening rates among New Mexico’s AI communities. Methods Guided by the principles of Community Based Participatory Research, we engaged providers from the two tribal healthcare facilities and tribal community members through focus group (two focus groups with providers (n = 15) and four focus group and listening sessions with community members (n = 65)), to elicit perspectives on the feasibility and appropriateness of implementing The Guide to Community Preventive Services (The Community Guide) recommended evidence-based interventions (EBIs) and strategies for increasing CRC screening. Within each tribal healthcare facility, we engaged a Multisector Action Team (MAT) that participated in an implementation survey to document the extent to which their healthcare facilities were implementing EBIs and strategies, and an organizational readiness survey that queried whether their healthcare facilities could implement additional strategies to improve uptake of CRC screening. Results The Community Guide recommended EBIs and strategies that received the most support as feasible and appropriate from community members included: one-on-one education from providers, reminders, small media, and interventions that reduced structural barriers. From the providers’ perspective, feasible and acceptable strategies included one-on-one education, patient and provider reminders, and provider assessment and feedback. Universally, providers mentioned the need for patient navigators who could provide culturally appropriate education about CRC and assist with transportation, and improved support for coordinating clinical follow-up after screening. The readiness survey highlighted overall readiness of the tribal facility, while the implementation survey highlighted that few strategies were being implemented. Conclusions Findings from this study contribute to the limited literature around implementation research at tribal healthcare facilities and informed the selection of specific implementation strategies to promote the uptake of CRC screening in AI communities.